METALL HALQANING MAGNIT MAYDONDA TUSHISHI MASALASI - Yavidov, B.; Esemuratova, Sh.; Madirimova, Sh.; Ro‘zimatov, D. (SCIENCE and SOCIETY, 2017)
In the article a task about falling of thin metallic wire in magnetic field is considered. Induction of the magnetic field grows together with the growth of with the height, while its direction is contrary to the direction of free fall acceleration. The author describes the method of finding of falling steady speed of the wire. The method used in solving the task has a universal character and can be used in solving the tasks connected with the movement of charges and currents.